Co-existence of Systemic Lupus Erythematosus and Ankylosing Spondylitis - A Case Report - Nakarmi, Shweta; Ahmed, Shamim; Shahin, Md Abu; Shazzad, Md Nahiduzzaman; Mahmood, Tareq; Haq, Syed Atiqul (Bangladesh Medical Journal, 2019)
Co-existence of systemic lupus erythematosus and ankylosing spondylitis is not common. In this report, we present a 24-year-old woman with both the entities diagnosed in the course of time. Initially she presented with malar rash, photosensitivity, oral ulcer and polyarthritis. Her ANA and anti-Smith antibody were positive, but ant-ds DNA was negative. With these features, she was diagnosed as a case of systemic lupus erythematosus. Few months later, she was diagnosed with ankylosing spondylitis on the basis of inflammatory back pain and bilateral sacroilitis. Bangladesh Med J. 2017 Sep; 46 (3): 100-103